THE EFFECT OF PROFITABILITY AND SOLVENCY ON COMPANY VALUE - Almas Ghassani, Tifani; Sulistiyo, Hari (Jurnal Ekonomi Balance, 2020)
Profitability and Solvency of Company Value partially and simultaneously at the Food & Beverage Company, the period used for 4 (four), namely 2015-2018. The data consists of financial statements on the Indonesia Stock Exchange (IDX) in Indonesia in 2015-2018. The data source used is secondary data, the population used in this study Food & Beverage Companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. The analysis used in this research is multiple linear regression, classic assumption test, descriptive statistics, determination analysis, and hypothesis testing. The results of the analysis of profitability data against company value. The obtained count value of 2,860 then when compared with a table of 2.032. Then the results obtained count or equal to 2,860> 2,032 received positively. Solvency to Company Value. Obtained count of 2,451 then when compared with table of 2.032. Then the results obtained count 2,451> table 2,032 received positive